SYSTEM DYNAMICS FOR SIMULATION MODEL OF MATERIAL COST IN WATER RECOURCES PROJECT - Mundra, I Wayan; Hirijanto, Hirijanto (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2020)
Project cost is one of the constraints in the achievement of a construction project. Limitation on projects financing require more realistic and efficient cost analysis in preparation of project. Due to changes in projects planning over time, it is usually difficult to predict the future project cost. So, we need an integrated system and give an efficiency for the planner. Project cost consists of cost components which is there are an interrelationship each other’s and influencing the overall cost of the project. The approach using system dynamic is one of the best solutions to identify the causal relationship between cost components by using software tools Ventana Simulation (Vensim) to facilitate the identification of causal relationship (causatic diagram) and mathematical equations between variables in stock flow diagram. The results of system dynamic approach show that the simulation model can be used to predict/ estimate the project’s cost in the coming years. Verification and validation of simulation model is eligible based on the value of means comparison, E1 = 0.32% < 5% and % error variance, E2 = 3.19% < 30% so the developed model can be done scenarios for changes that occur on the system according to the user needs.